2019
DOI: 10.31002/jalspro.v3i2.2036
|View full text |Cite
|
Sign up to set email alerts
|

Composition of Cow Milk Kefir Enriched with Ginger Extract (Zingiber officinale)

Abstract: This study aims to analyze the addition of ginger extract (Zingiber officinale) to the composition of cow's milk kefir. Kefir is made from cow's milk with 10% (w/w) kefir grains and ginger extract at intervals of 0, 0.5, 1.0, 1.5 and 2.0% (w/w), all treatments are incubated at room temperature for 24 hours. Kefir composition that was observed was water content, ash content, protein content, and fat content. The results showed that the addition of ginger extract did not affect the composition (water content, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
0
2
4
Order By: Relevance
“…We observed the decrease on days 7 and 14 of storage that could be associated with the growing fungi. Compared to previous findings, the mean of total solids in this study was 17.39% higher than 12.09%, 12.37%, and 14.59 from goat milk kefir (Cais-Sokolińska et al, 2015;Satir & Guzel-Seydim, 2016;Setyawardani et al, 2014), 9.49% from ginger-added cow milk kefir (Wulansari & Rahayu, 2019) and 14.84% from cow colostrum kefir (Setyawardani et al, 2020).…”
Section: Chemical Characteristicscontrasting
confidence: 88%
“…We observed the decrease on days 7 and 14 of storage that could be associated with the growing fungi. Compared to previous findings, the mean of total solids in this study was 17.39% higher than 12.09%, 12.37%, and 14.59 from goat milk kefir (Cais-Sokolińska et al, 2015;Satir & Guzel-Seydim, 2016;Setyawardani et al, 2014), 9.49% from ginger-added cow milk kefir (Wulansari & Rahayu, 2019) and 14.84% from cow colostrum kefir (Setyawardani et al, 2020).…”
Section: Chemical Characteristicscontrasting
confidence: 88%
“…It confirms the required fat levels for kefir products according to Standard Codex, i.e., less than 10% (12). The average fat in this study was higher than that 0.38% in kefir whey (15), 2.09% in kefir made of colostrum goat milk (13), and kefir made of additional ginger extract (3.175) (21).…”
Section: Resultscontrasting
confidence: 62%
“…Table 1 shows that moringa leaf powder does not affect the total solid (P>0.05). The average total solid in this study is 18.17%, which is higher than the previous findings on goat milk, namely 12.09% (19) and 12.37% (20), as well as 9.49% in kefir plus ginger extract (21). The kefir product in this study has met the standard quality of fermented milk products assigned by BSN, i.e., a minimum of 3% (22).…”
Section: Resultscontrasting
confidence: 57%
See 1 more Smart Citation
“…However, the fortification with both extracts induced negative sensory results compared to the control. Similarly, Wulansari et al [19] reported that the addition of ginger extract (2%) did not affect the composition of kefir in terms of water, ash, protein, and fat content.…”
Section: Plant Extracts For Kefir Enrichmentmentioning
confidence: 91%